Symphonic categories "sublime" and "beautiful" in the Byzantine theological and aesthetic traditions: semantic aspect - A. I. Matytsyn (Ukrainian Cultural Studies, 2017)
The article is devoted to the considering of the definition of categories of "sublime" and "beautiful". The basic features of the categories of "sublime" and "beautiful" as an extremely complex and have a large volume. The symphonicity of these categories is analyzed. The possibilities and the context of their use are shown. It is proved that the dialectical nature of the process of the unfolding of these concepts in the context of the aesthetic thought of Byzantium is due to the presence of elements similar to the principles of modern humanism are defined as principles that characterize symphonism as a special quality of thinking. The following universal characteristics of Byzantine culture are defined as symphonic and canon. A detailed explanation of the connection between the categories "sublime" and "beautiful" is given in the context of the Byzantine theological-aesthetic tradition. The article proves that the connection between the categories "sublime" and "beautiful" can and does occur within the framework of the Byzantine canon through their symphony, consonance in the context of the divine. It is determined that the transition from a literal understanding of a sign or symbol to metaphorical one requires an understanding of certain rules and conventions that arise in the course of this transition. It is especially important that the symphony, the harmony of the categories "beautiful" and "sublime", that being extremely voluminous in their content, at the same time make it possible for the ordinary man to perceive complex symbolic systems. The common feature of the categories "beauty", "beautiful" and "sublime" within the aesthetics of Byzantium is not only the inclusion of the sign "value" (νόημα) as elements in the goal, but also their use. As an additional, intermediate link in the connection symbol(in the aesthetics of Byzantium it is more of an artistic symbol) - a person who is the central axis of the aesthetics of Byzantium. It is proved that the category in linguistics has linguistic meanings that are interconnected because of the common semantic features, and they are such that represent a closed system of elements of these attributes. In our case, the categories "sublime" and "beautiful" include the entire spectrum of elements that we call when defining these concepts.